Fabry Disease: The Current Treatment Landscape - Lenders, Malte (Drugs, 2021)
Fabry disease (FD) is a rare X-linked lysosomal storage disease based on a deficiency of α-galactosidase A (AGAL) caused by mutations in the α-galactosidase A gene (GLA). The lysosomal accumulation of glycosphingolipids, especially globotriaosylceramide (Gb(3)) and globotriaosylsphingosine (lyso-Gb(3), deacylated form), leads to a multisystemic disease with progressive renal failure, cardiomyopathy with potentially malignant cardiac arrhythmias, and strokes, which considerably limits the life expectancy of affected patients. Diagnostic confirmation in male patients is based on the detection of AGAL deficiency in blood leukocytes, whereas in women, due to the potentially high residual enzymatic activity, molecular genetic detection of a causal mutation is required. Current treatment options for FD include recombinant enzyme replacement therapy (ERT) with intravenous agalsidase-alfa (0.2 mg/kg body weight) or agalsidase-beta (1 mg/kg body weight) every 2 weeks and oral chaperone therapy with migalastat (123 mg every other day), which selectively and reversibly binds to the active site of AGAL, thereby correcting the misfolding of the enzyme and allowing it to traffic to the lysosome. These therapies enable cellular Gb(3) clearance and improve the burden of disease. However, in about 40% of all ERT-treated men, ERT can lead to infusion-associated reactions and the formation of neutralizing antidrug antibodies, which reduces the efficacy of therapy. In chaperone therapy, there are carriers of amenable mutations that show limited clinical success. This article provides a brief overview of the clinical picture in FD patients, diagnostic confirmation, and interdisciplinary clinical management of FD. The focus is on current and future therapeutic options.